Effect of heat treatments on the strength and stiffness of poplar - Tuğba Yılmaz Aydın; Murat Aydın; Uğur Özkan (Maderas: Ciencia y Tecnología)
The influence of environmental conditions on wood material properties is known. Temperature is one of them and its effect on poplar wood has been examined in a limited way which this study tried to figure out this issue in a limited context. The influence of heat treatment (110 °C, 160 °C, and 210 °C for 3 h and 6 h) on the density, ultrasonic wave velocity, modulus of rupture, and modulus of elasticity of poplar wood was evaluated. A 2,25 MHz longitudinal ultrasonic wave was used to determine both the ultrasonic wave velocity and the dynamic modulus of elasticity. A three-point bending test was conducted to determine the static modulus of elasticity and the modulus of rupture. The average values for the control samples were 350 kg/m³ for density, 3 598 m/s for ultrasonic wave velocity, 4 552 MPa for dynamic modulus of elasticity, 5 864 MPa for static modulus of elasticity, and 64,1 MPa for modulus of rupture. When samples were treated at 210 °C for 6 h, these properties decreased by 14,3 %, 3 %, 18,7 %, 25 %, and 50,2 %, respectively. In general, the dynamic modulus of elasticity values were lower than the static ones across all treatment conditions. The greatest difference between dynamic and static modulus (34 %) was observed at 110 °C for 6 h, while the smallest difference (18,8 %) occurred at 210 °C for 6 h. Improvements of up to 8,9 %, 2,4 %, and 0,85 % were observed in the modulus of rupture, static modulus of elasticity, and ultrasonic wave velocity, respectively, at 110 °C treatments.